Legacy phone networks get new lease on life a telecom evolution caters to data demands. - Testa, B.M (IEEE spectrum)
Perhaps the biggest technical problem facing telephone companies all over the world is the growing mismatch between their networks' capabilities and customer demands. Nowhere is this mismatch more glaringly apparent than in the companies' struggle to keep pace with the steady growth of Internet traffic. Pure data now exceeds voice traffic nearly everywhere, over the legacy phone systems designed decades ago and optimized for an entirely different purpose-the handling of digitized voice signals. The author discusses the introduction of SONET together with the boosting of its speed and virtual concatenation. The paper concludes by considering how to cut SONET costs.